(untitled) (International Journal of Engineering and Computer Science, 2017)
In a Homeopathic Consultancy, a patients records are maintained manually, which requires lot of time for searching and updating. Even the communication order to reduce this time requirement & introduce a smooth Doctor-Patient interaction, we need to digitize the whole system. This will result in much more efficient consumption of the resources, viz. time, stationery and man-power. An Android based app will be developed, providing humongous number of features to both, Doctor and Patients. Even the communication process between the Doctor and Medicine Room will be digitized. A confidential database containing the whole CASE-FILES of a respective Patients will be made using MySQL and SQLite. This database could be accessed by the Doctor only. By deploying the database on a Cloud, we will ensure portability, mobility and flexibility in accessing the same for the Doctor. The FrontEnd, i.e. the App will be interfaced by the database using Web Server